Perceived deterrents to being a plasmapheresis donor in a voluntary, nonremunerated environment. Issue 5 (24th September 2012) - Bagot, Kathleen L.; Bove, Liliana L.; Masser, Barbara M.; Bednall, Timothy C.; Buzza, Mark
<x xml:space="preserve">Abstract</x> BACKGROUND: As demand for plasma‐derived products increases internationally, maintaining a committed plasmapheresis panel membership is critical for blood collection agencies. This study addresses the current lack of knowledge regarding deterrents to the recruitment and retention of plasmapheresis donors in a voluntary nonremunerated environment. STUDY DESIGN AND METHODS: Nine focus groups (n = 84) and six individual interviews were conducted using semistructured schedules. Three focus groups were conducted with each category of eligible whole blood (WB) donors: those who had 1) declined to convert to plasmapheresis (DTC), 2) converted but lapsed to WB (LWB), and 3) converted and lapsed from the panel completely (LFP). Transcript analysis revealed distinct deterrent categories. RESULTS: The time required for plasmapheresis was a universally identified deterrent, with concerns of donation frequency expectations shared between DTC and LWB. LWB and LFP both reported excessive questioning and paperwork, and eligibility requirements as deterrents. Unique deterrents for DTC were a lack of accurate knowledge about safety and process. LWB reported concerns about plasmapheresis donation outcomes; however, they were more committed to continuing donation than LFP, who reported donation not being salient, being too busy, and poorer donation experiences. CONCLUSION: Providing information to address safety and health concerns should be the focus for successful conversion to plasmapheresis. Setting donation frequency expectations at levels to which donors are accustomed may improve evaluations of the cost/benefit ratio of conversion and retention. Involvement levels (i.e., importance, personal meaning of donation) may be the key differentiator between those donors who return to WB and those that lapse altogether.